FINDING THE MAXIMUM AND MINIMUM VALUE OF A FUNCTION ON A SEGMENT (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Finding the maximum and minimum value of a function in a given segment is an important aspect of calculus. This article discusses various methods and techniques used to determine the largest and smallest values of a function within a specified range. The article explores the concepts of local maximum and minimum, as well as global maximum and minimum, and provides examples and practical applications to illustrate the process.